Risk Management Analysis in Credit Provision to Minimize Bad Debts at PT. Bank Rakyat Indonesia (Persero) Tbk. Banggai Unit - Tagoe, Chika Olivia; Mawikere, Lidia M.; Latjandu, Lady Diana (Formosa Journal of Applied Sciences, 2024)
Credit provision is one of the main activities of banks that has risks, especially related to Non-Performing Loans (NPL). The purpose of providing credit is to help customers develop their business, working capital and investment. In addition, credit provision also aims to gain profit. This profit is obtained from the interest given to customers by the bank as a form of remuneration for providing loans. The purpose of this study is to analyze the effectiveness of risk management in providing credit at PT. Bank Rakyat Indonesia (Persero) Tbk. Banggai Unit to minimize the occurrence of bad debts. The method used in this study is a qualitative descriptive method, with data obtained through interviews and documentation at BRI Unit Banggai. The results of this study indicate that BRI Unit Banggai has implemented credit risk management principles, such as risk identification, risk analysis, risk assessment, solution implementation, and periodic risk monitoring.